Active fault-tolerant load frequency control for multi-area power systems with electric vehicles under deception attacks - Liu, Xinghua (2024)
This paper studies the active fault tolerant load frequency control of multi-area power systems with electric vehicles under deception attacks. An integrated design of fault estimation and fault-tolerant control is proposed to guarantee the stability of the system under sensor faults and deception attacks. Considering the uncertainty caused by the demand of the owner and the state of the battery, a multi-area power system model is proposed. Then, an active fault tolerant load frequency control scheme is designed. The proportional-derivative sliding mode observer is used to estimate the fault and system status in real-time. During the fault occurrence, the estimated value obtained by the observer is utilized to design the controller without any fault diagnosis scheme, which simplifies the controller design process. A sufficient Lyapunov-Krasovskii criterion is derived to ensure the stability performance of the multi-area power system. Finally, simulation examples are provided for a three-area power system contains electric vehicles, and the results prove the correctness and feasibility of the proposed fault-tolerant control scheme.